Optimalisasi Pengolahan Air Limbah Dengan Menggunakan Metode Ozon Microbubble Untuk Menurunkan Kadar COD (Chemical Oxygen Demand) Dan TSS (Total Suspended Solid) Di PT Industri Kimia - Aji Susanto; Karina Imelda; Dodit Ardiatma; Nur Ilman Ilyas (Prosiding Sains dan Teknologi, 2022)
This study aims to determine the effect of variations in contact time on decreasing levels of Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) using Ozone Microbubble and determine the efficiency level of Ozone Microbubble. This research uses liquid waste from WWTP at PT. Chemical Industry Cikarang with variations in processing time of 20, 40, 60 minutes. The test results before the Ozone Microbubble method was applied did not meet the quality standards and after being applied with a time variation of 20, 40, 60 minutes, they met the Hyundai Industrial Estate wastewater quality standards. The decrease for COD levels with a time of 60 minutes was 614.6 mg/L. Meanwhile, the TSS level is 170.8 mg/L. Both still meet the quality standards of the Hyundai Industrial Estate. The efficiency level for COD is 33% and TSS is 32%. From the results of reducing COD and TSS, it can be concluded that the use of Ozone Microbubble can be used in chemical waste. In addition to the relatively high percentage of reduction, in terms of costs in this research, it is also relatively cheap and can be a proposed idea if it is to be implemented. Keywords: Ozon, Microbubble, Chemical Industry Liquid Waste, COD, TSS